Образи Христа й Богородиці в поезії Григорія Сковороди і Віри Вовк - Григорчук, Ю. (Слово і Час, 2022)
У статті здійснено порівняльний аналіз євангельських образів у доробку
поетів XVIII і ХХ—ХХІ ст. Зазначено, що образ Спасителя у віршах
митців візуально не конкретизований, однак семантично глибокий. Це
виражають символи слова, каменя, зернини (у Г. Сковороди) та іпостасі
Христа-Садівника, Лікаря, Керманича на Черемоші (у Віри Вовк). Сукупно
вони творять єдину цілісність символічного образу, однак якщо філософові притаманне барокове, біблійно-церковне, то поетесі — модерністське,
авторське трактування постаті Месії. Зазначено, що образ Богородиці у
Г. Сковороди менш виражений, ніж образ Ісуса, і розкритий лише у трьох
віршах, тоді як у Віри Вовк Діві Марії присвячено три окремі збірки. Установлено, що спільною для поезії цих авторів є іпостась Богородиці-Матері.
Окреслено особливості художньої інтерпретації образу. Підсумовано
своєрідність авторської рецепції постатей Христа й Богородиці, розкрито їхнє морально-аксіологічне наповнення й біблійне підґрунтя. The paper analyzes the images of Jesus Christ and the Mother of God in the poetry by Hryhorii
Skovoroda and Wira Wowk. Until now, this topic has not been the object of scholarly research
although the creativity of writers has many common features: aphoristic style, philosophical
mood, and biblical figurative elements. The purpose of the paper is to characterize the specifics
of interpreting the images of Christ and the Mother of God in the authors’ poetry. The analysis
is based on the collections “The Garden of Divine Songs” by H. Skovoroda and “The Rosary for
Christ”, “The Rosary for the Mother of God” by Wira Wowk.
Peculiar in the reception of the figure of Christ in the poetry of both authors is its outer
featurelessness and deep semantic content. H. Skovoroda used the concepts of ‘life’, ‘joy’,
‘pure heart’ and the biblical symbols of fire, stone, word, and grain; Wira Wowk preferred
the symbols of word, light, heart, and ear of corn. Each author is characterized by the original
interpretation of the biblical image of the Savior. He is embodied in the figures of a guest,
an astronomer, a doctor hurt for human faults (poetry by H. Skovoroda) and a doctor, a
heavenly gardener, a helmsman on Cheremosh (poetry by Wira Wowk).
The image of the Virgin in H. Skovoroda’s work is less pronounced than the image
of Jesus and is revealed only in three poems, while Wira Wowk dedicated three separate
collections to the Virgin Mary. There are different symbolic hypostases of the Mother of God
in the poems by H. Skovoroda, which have been singled out. Wira Wowk’s interpretation
of this image is characterized by such features as iconographic specification, biblical
dynamics of unfolding, and symbolic content (images of the Winged Mother of God, the
Mother Princess, Lilia, Oranta). The image of Mother Mary is common to both authors
(Mary, Mother of Jesus — in Skovoroda’s poems and Mother of humanity, the world, and
Ukraine — in Wira Wowk’s ones).
Special attention has been paid to the biblical prototext in the poetic works by
H. Skovoroda and Wira Wowk, important in the interpretation of the figures of Christ and
the Mother of God, as well as to the moral and axiological depth of these images and their
conceptual significance.